2018
DOI: 10.1093/jxb/ery096
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Anthocyanins in Petioles codes for a GST anthocyanin transporter that is essential for the foliage and fruit coloration in strawberry

Abstract: Reduced Anthocyanins in Petioles (RAP) encodes a glutathione S-transferase anthocyanin transporter that is essential for the foliage and fruit coloration in strawberry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
153
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(173 citation statements)
references
References 65 publications
20
153
0
Order By: Relevance
“…Heterologous overexpression of VviGST4 ( Vitis vinifera ) and AcGST1 ( Actinidia chinensis ) in Arabidopsis tt19 mutant can functionally complement both the anthocyanin‐less phenotype in plant and the PA‐deficient phenotype in seed coat (Liu et al , ; Pérez‐Díaz et al , ). However, in this study, PpGST1 only possessed the capacity to functionally complement the anthocyanin‐less phenotype of Arabidopsis tt19 mutant but not the PA‐deficient phenotype in the seed coat, which was similar to the result of An9 ( Petunia hybrida ), LcGST4 ( Litchi chinensis ), RAP ( Fragaria ananassa ), CsGSTF1 ( Camellia sinensis ) and MdGSTF6 ( Malus domestica ) in the tt19 complementation assay (Hu et al , ; Jiang et al , ; Kitamura et al , ; Luo et al , ; Wei et al , ). These data indicated that PpGST1 plays a pivotal role in anthocyanin transport and differed from AtTT19 , VviGST4 and AcGST1 which also participate in seed deposition of PAs.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Heterologous overexpression of VviGST4 ( Vitis vinifera ) and AcGST1 ( Actinidia chinensis ) in Arabidopsis tt19 mutant can functionally complement both the anthocyanin‐less phenotype in plant and the PA‐deficient phenotype in seed coat (Liu et al , ; Pérez‐Díaz et al , ). However, in this study, PpGST1 only possessed the capacity to functionally complement the anthocyanin‐less phenotype of Arabidopsis tt19 mutant but not the PA‐deficient phenotype in the seed coat, which was similar to the result of An9 ( Petunia hybrida ), LcGST4 ( Litchi chinensis ), RAP ( Fragaria ananassa ), CsGSTF1 ( Camellia sinensis ) and MdGSTF6 ( Malus domestica ) in the tt19 complementation assay (Hu et al , ; Jiang et al , ; Kitamura et al , ; Luo et al , ; Wei et al , ). These data indicated that PpGST1 plays a pivotal role in anthocyanin transport and differed from AtTT19 , VviGST4 and AcGST1 which also participate in seed deposition of PAs.…”
Section: Discussionsupporting
confidence: 73%
“…For example, LcGST4 was involved in anthocyanin transport in litchi (Hu et al , ). In strawberry, RAP encodes a GST protein critical for anthocyanin accumulation in fruit and foliage (Luo et al , ). In grapevine, VviGST3 is related to PA transport while VviGST4 is pivotal for both anthocyanin and PA accumulation (Pérez‐Díaz et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Other TFs for which expression was correlated with flavonoid metabolism, such as TCP1 ( FvH4_6g16170 ), ZFN2 (FvH4_7g01060) and DIV (FvH4_6g11950) (Pillet et al , ), were down‐regulated in transgenic red receptacles (Table S2). In contrast, other genes associated with anthocyanin production in strawberry, such as the four members of the RAP family ( FvH4_1g27460 , FvH4_6g38760 , FvH4_2g25200 , FvH4_2g25210 ), encoding GST anthocyanin transporters (Luo et al , ), were up‐regulated in white receptacles of the silenced lines.…”
Section: Metabolic Changes In the Receptacles Of Famads9‐silenced Linmentioning
confidence: 92%
“…Polyphenolic compounds are known to strongly interact with proteins sometimes without any specificity (Adamczyk et al, 2017), while the interaction of GST293 with the flavonoid-derived compounds could be more specific. Indeed, it has already been shown that plant phi GSTs are able to conjugate glutathione to cyanidin 3-glucoside to form a conjugate that is then transported to the vacuole via tonoplast Mg-ATP-requiring glutathione pumps (Alfenito et al, 1998;Luo et al, 2018). The interaction of GST293 will be studied more in detail but one can hypothesize that it could be involved in the transport and the solubilization of such compounds in the context of wood extractive detoxification.…”
Section: Intradiol Ring-cleavage Dioxygenasesmentioning
confidence: 99%